MicroRNA-223 Attenuates Stretch-Injury-Induced Apoptosis in Brain Microvascular Endothelial Cells by Regulating RhoB Expression - Yingliang Liu; Wenjing Li; Yingxiu Liu; Yang Jiang; Yida Wang; Zhiming Xu; Daming Cui; Liang Gao (Brain Sciences, 2022)
MiR-223 is a miRNA with important functions in apoptosis, carcinogenesis, and inflammation, and it was demonstrated to be over-expressed in brain tissue after traumatic brain injury (TBI). However, few studies have focused on its role in protecting brain microvascular endothelial cells (BMECs). This study evaluated the protective effect of miR-223 on BMECs after stretch injury (SI). bEnd.3 cells (BMECs of mouse) were transfected with overexpressing and blocking lentivirus of miR-223, then were subjected to SI. After immunofluorescence assay, it was demonstrated that miR-223 overexpression significantly rescued the SI-induced loss of ZO-1 (Zonula Occludens 1, tight junction protein) (p < 0.01), while miR-223 blocking exacerbated the loss of ZO-1 (p < 0.05). Flow cytometry confirmed a significant increase in the proportion of apoptotic bEnd.3 cells after SI, and miR-223 overexpression reduced this proportion (p < 0.001). The result of Western blot revealed that miR-223 overexpression significantly reduced the expression of cleaved caspase-3 (cl-caspase 3) (p < 0.05) and RhoB (p < 0.01), while miR-223 blocking increased the expression of these proteins (p < 0.05, p < 0.001). Additionally, knockdown of RhoB significantly reduced the expression of cl-caspase 3 (p < 0.001). These findings suggested that miR-223 can alleviate SI-induced apoptosis of BMECs, and this anti-apoptotic effect is at least partially achieved by inhibiting the expression of RhoB. Moreover, miR-223 may play a role in maintaining the integrity of BBB during TBI.